Prospective Uses of Genetically Engineered Lactic Acid Bacteria for the Prevention of Inflammatory Bowel Diseases - LeBlanc, Jean Guy; Carmen, Silvina del; Lima, Fernanda Alvarenga; Turk, Meritxell Zurita; Miyoshi, Anderson; Azevedo, Vasco; LeBlanc, Alejandra de Moreno de (IntechOpen, 2012)
None